The Development Science of Physics Question Bank High Order Thinking Skill (HOTS) to Olympiad of Science in Elementary School - Junaidi, Nurhikmah Sasna; Asra, Azmi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The learning science at Junior High School can be supported by the experience of learning. The research of purpose was to develop Science of Physics Question Bank High Order Thinking Skills (HOTS) to Olympiad of Science in Elementary School with valid, practical, and effective criteria. The type of research was Reeves model which consists of four phases: analysis problem, design and development phases, Iterative cycles of testing and refinement, and the implementation phases. The Population of research the students' Olympiad team in Rambah of the district. Data of this research were obtained through questionnaires, validation sheets, practicalities, and achievement tests. The data analysis used was descriptive. Important information which obtained for analysis problem was to develop the Science Physics Question Bank High Order Thinking Skill (HOTS) to Olympiad of Science in Elementary School. The validity of the developed question bank was determined by the expert review which involved four validators. Whereas, the practicality of that question bank was determined by one-to-one, small group, and field test evaluation. Effectivity analysis showed that the category of question banks was very effective to improve high and critical thinking skills (HOTS) of knowledge. It is concluded that the science of physics question bank High Order Thinking Skills (HOTS) to Olympiad of science in Elementary School was already fulfilled the criteria of valid, practical, and effective.